ASSESSING THE INFLUENCE OF CLIMATE VARIABILITY ON POULTRY PRODUCTION IN MAIDUGURI, BORNO STATE, NIGERIA - Aliyu, Y.M.; Mudi, Z.A.; Thamus, Z.Y. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examines the socio-economic characteristics of poultry farmers and the influence of climate variability on poultry production in Maiduguri, Borno State, Nigeria. A structured questionnaire was used to collect data from 240 respondents. The findings reveal that poultry farming is predominantly male-dominated (63.8%), with most farmers aged between 31–40 years (40.0%). Educational attainment is relatively high, with 37.5% of respondents having tertiary education. Farm ownership is mainly through hiring (45.0%), and 50.0% of farmers have between 6–10 years of experience in poultry rearing. Climate variability significantly affects poultry production. High temperatures increase respiration and fluid loss in birds (60.0%), while excessive air circulation spreads diseases (40.0%) and damages poultry housing (42.7%). Rainfall leads to pest and disease proliferation (60.0%), while cloud cover reduces egg production (73.3%). High atmospheric pressure negatively impacts poultry growth and oxygen availability. Regression analysis indicates that socio-economic factors such as age (p = 0.005), household size (p = 0.003), education level (p = 0.002), farm ownership (p = 0.005), and poultry rearing experience (p = 0.002) significantly influence production (R² = 0.85). Major constraints include high feed prices (13.3%), high mortality rates (14.7%), sudden weather changes (10.7%), and middlemen interference (10.7%). To enhance poultry productivity and resilience to climate variability, farmers should adopt improved poultry housing with proper ventilation and insulation. Government and private sectors should support climate adaptation strategies and provide affordable veterinary and extension services.